Impact of risk factor control on peripheral artery disease outcomes and health disparities. (August 2022) - Pohlman, F Will; Ford, Cassie B; Weissler, E Hope; Smerek, Michelle M; Hardy, N Chantelle; Narcisse, Dennis I; Lippmann, Steven J; Greiner, Melissa A; Long, Chandler; Rymer, Jennifer A; Gutierrez, J Antonio; Patel, Manesh R; et al.
Background: Peripheral artery disease (PAD) is associated with modifiable atherosclerotic risk factors like hypertension, diabetes, hyperlipidemia, and smoking. However, the effect of risk factor control on outcomes and disparities in achieving control is less well understood. Methods: All patients in an integrated, regional health system with PAD-related encounters, fee-for-service Medicare, and clinical risk factor control data were identified. Component risk factors were dichotomized into controlled and uncontrolled categories (control defined as low-density lipoprotein < 100 mg/dL, hemoglobin A1c < 7.0%, SBP < 140 mmHg, and current nonsmoker) and composite categories (none, 1, ⩾ 2 uncontrolled RFs) created. The primary outcome was major adverse vascular events (MAVE, a composite of all-cause mortality, myocardial infarction, stroke, and lower-extremity revascularization and amputation). Results: The cohort included 781 patients with PAD, average age 72.5 ± 9.8 years, of whom 30.1% were Black, and 19.1% were Medicaid dual-enrolled. In this cohort, 260 (33.3%) had no uncontrolled risk factors and 200 (25.6%) had two or more uncontrolled risk factors. Patients with the poorest risk factor control were more likely to be Black ( p < 0.001), Medicaid dual-enrolled ( p < 0.001), and have chronic limb-threatening ischemia ( p = 0.009). Significant differences in MAVE by degree of risk factor control were observed at 30 days (none uncontrolled: 5.8%, 1 uncontrolled: 11.5%, ⩾ 2 uncontrolled: 13.6%; p = 0.01) but not at 1 year ( p = 0.08). risk factor control was not associated with outcomes at 1 year after adjustment for patient and PAD-specific characteristics. Conclusions: risk factor control is poor among patients with PAD. Significant disparities in achieving optimal risk factor control represent a potential target for reducing inequities in outcomes.